Apa Urgensi Omnibus Low di Indonesia? - Nur, Mohamad Ichsana (Jurnal Review Politik, 2021)
Omnibus Enforcement of Law will soon be held in Indonesia, several countries have certain characteristics not least in Indonesia, In Indonesia itself, is still being reformed until now, will be enactment of the Omnibus Law itself. This research discusses to improve and effectively discuss and variables on the legal system and political system in Indonesia. With using qualitative methods and using Social Research methods, so the Omnibus Theory itself comes from countries that adhere to the general legal system. However, considering the Omnibus of Law is still less known among the academic community in Indonesia. For the reason, the meaning of this paper is to discuss Omnibus Law and its use to address the problem of requirements in Indonesia.